Resveratrol and beyond: The Effect of Natural Polyphenols on the Cardiovascular System: A Narrative Review - Roland Gál; Róbert Halmosi; Ferenc Gallyas; Michael Tschida; Pornthira Mutirangura; Kálmán Tóth; Tamás Alexy; László Czopf (Biomedicines, 2023)
Cardiovascular diseases (CVDs) are among the leading causes of morbidity and mortality worldwide. Unhealthy dietary habits have clearly been shown to contribute to the development of CVDs. Beyond the primary nutrients, a healthy diet is also rich in plant-derived compounds. Natural polyphenols, found in fruits, vegetables, and red wine, have a clear role in improving cardiovascular health. In this review, we strive to summarize the results of the relevant pre-clinical and clinical trials that focused on some of the most important natural polyphenols, such as resveratrol and relevant flavonoids. In addition, we aim to identify their common sources, biosynthesis, and describe their mechanism of action including their regulatory effect on signal transduction pathways. Finally, we provide scientific evidence regarding the cardiovascular benefits of moderate, long-term red wine consumption.